Solving ordinary differential equations to understand luminescence: ‘RLumModel’, an advanced research tool for simulating luminescence in quartz using R - Friedrich, Johannes; Kreutzer, Sebastian; Schmidt, Christoph (Quaternary geochronology, 2016)
Kinetic models of quartz luminescence have gained an important role for predicting experimental results and for understanding charge transfers in (natural) quartz. Here we present and discuss the new R package ‘RLumModel’, offering an easy-to-use tool for simulating quartz luminescence signals (TL, OSL, LM-OSL and RF) based on five integrated and published parameter sets. Simulation commands can be created (a) using the Risø Sequence Editor, (b) a built-in SAR sequence generator or (c) self-explanatory keywords for customised sequences. Results can be analysed seamlessly using the R package ‘Luminescence’ along with a visualisation of concentrations of electrons and holes in every trap/centre as well as in the valence and conduction band during all stages of the simulation. Examples of simulated luminescence phenomena and dating protocols are given, and the presented code snippets are available in the supplementary material. Package and source code are provided under the General Public Licence (GPL-3) conditions.
Online verfügbar: 27. Mai 2016, Artikelversion: 16. Juli 2016
Gesehen am 31.03.2025